2016
DOI: 10.1073/pnas.1619067114
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of 19S proteasome subunits marks emergence of an altered cell state in diverse cancers

Abstract: The use of proteasome inhibitors to target cancer’s dependence on altered protein homeostasis has been greatly limited by intrinsic and acquired resistance. Analyzing data from thousands of cancer lines and tumors, we find that those with suppressed expression of one or more 19S proteasome subunits show intrinsic proteasome inhibitor resistance. Moreover, such proteasome subunit suppression is associated with poor outcome in myeloma patients, where proteasome inhibitors are a mainstay of treatment. Beyond conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 37 publications
8
39
2
Order By: Relevance
“…For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB). These subunits have been shown to be key players across different cancers (Rouette et al, 2016;Tsvetkov et al, 2017;Li et al, 2017). We also observed significant associations for RELA (also known as Transcription Factor p65) in all of the studied cancers which aligns with its oncogenic role across different cancers (Collignon et al, 2018), and moreover, with its reported associations with Bortezomib in breast cancer (Hideshima et al, 2014), prostate cancer (Manna et al, 2013), and lung cancer (Zhao et al, 2015).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 75%
“…For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB). These subunits have been shown to be key players across different cancers (Rouette et al, 2016;Tsvetkov et al, 2017;Li et al, 2017). We also observed significant associations for RELA (also known as Transcription Factor p65) in all of the studied cancers which aligns with its oncogenic role across different cancers (Collignon et al, 2018), and moreover, with its reported associations with Bortezomib in breast cancer (Hideshima et al, 2014), prostate cancer (Manna et al, 2013), and lung cancer (Zhao et al, 2015).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 75%
“…In this Lo19S state, cells exhibit an enhanced ability to tolerate the toxic effects of many proteasome inhibitors. This resistance mechanism has been observed in experimental model systems and in a variety of tumors recovered from patients (Acosta-Alvear et al, 2015;Nijhawan et al, 2012;Tsvetkov et al, 2017). Prominently, multiple myeloma patients that are refractory to proteasome inhibitors most often have tumors with the spontaneously reduced expression of 19S subunits (Acosta-Alvear et al, 2015;Tsvetkov et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Several recent studies using different genetic approaches have converged on a novel mechanism that allows cells to cope with the proteotoxic stress induced by proteasome inhibitors (Acosta-Alvear et al, 2015;Shi et al, 2017;Tsvetkov et al, 2015;Tsvetkov et al, 2017). The 26S proteasome complex consists of the catalytic barrel where proteins are processed (20S complex) that can be capped with either one or two 19S regulatory complex caps that include the ubiquitin-regulating enzymes and protein unfolding ATPases (Budenholzer et al, 2017;Coux et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the turnover of ubiquitin-dependent WT-CyclinB1-NT slowed-down in hypoxic cells (Figure 2E) correlated with 26S proteasome disassembly ( Figure 1B). The 19S RP provides the ATP-and ubiquitin-dependency to the 26S proteasome; hence, a useful approach to decipher the 20S proteasome role in cells, is to deplete 19S RP subunits (Tsvetkov et al, 2015;Tsvetkov et al, 2017). In order to elucidate the contribution of the two proteasome species towards ubiquitin-independent proteolysis, we adapted a model system for altered proteasome ratio (Tsvetkov et al, 2015;Tsvetkov et al, 2017) by knocking down PSMD2 in HEK293T cells (Figure 2F).…”
Section: Figure 1 Hypoxia Induced Proteasome Disassembly Leads To Ramentioning
confidence: 99%
“…The 19S RP provides the ATP-and ubiquitin-dependency to the 26S proteasome; hence, a useful approach to decipher the 20S proteasome role in cells, is to deplete 19S RP subunits (Tsvetkov et al, 2015;Tsvetkov et al, 2017). In order to elucidate the contribution of the two proteasome species towards ubiquitin-independent proteolysis, we adapted a model system for altered proteasome ratio (Tsvetkov et al, 2015;Tsvetkov et al, 2017) by knocking down PSMD2 in HEK293T cells (Figure 2F). By this doxycycline (Dox) inducible system, we generated clones with low levels of 30S and 26S proteasomes but elevated levels of 20S proteasome (Hi20S cells) ( Figure 2G).…”
Section: Figure 1 Hypoxia Induced Proteasome Disassembly Leads To Ramentioning
confidence: 99%